2017
DOI: 10.3390/cli5010002
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Multi-Source Weighted-Ensemble Precipitation (MSWEP) Product over India

Abstract: Error characterization is vital for the advancement of precipitation algorithms, the evaluation of numerical model outputs, and their integration in various hydro-meteorological applications. The Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) has been a benchmark for successive Global Precipitation Measurement (GPM) based products. This has given way to the evolution of many multi-satellite precipitation products. This study evaluates the performance of the newly relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 35 publications
(24 reference statements)
2
22
0
Order By: Relevance
“…Blue Nile, Colombian Andes, Peruvian Andes, and Taiwan), MSWEP performance is the worst relative to other SPPs when we consider MRE and CRMSE metrics; it has the highest overestimation for lower precipitation values and the highest underestimation for higher values. This outcome aligns with findings by Zambrano-Bigiarini and others [49], and by Nair and Indu [50]. Zambrano-Bigiarini and others [49] evaluated multiple SPPs over complex terrain over Chile, including MSWEP, CMORPH, and TMPA.…”
Section: Discussionsupporting
confidence: 84%
“…Blue Nile, Colombian Andes, Peruvian Andes, and Taiwan), MSWEP performance is the worst relative to other SPPs when we consider MRE and CRMSE metrics; it has the highest overestimation for lower precipitation values and the highest underestimation for higher values. This outcome aligns with findings by Zambrano-Bigiarini and others [49], and by Nair and Indu [50]. Zambrano-Bigiarini and others [49] evaluated multiple SPPs over complex terrain over Chile, including MSWEP, CMORPH, and TMPA.…”
Section: Discussionsupporting
confidence: 84%
“…However, many studies considered only a single P dataset (e.g., Scheel et al, 2011;Nair and Indu, 2017) or disregarded (re)analysis-based P datasets (e.g., Moazami et al, 2013;Mei et al, 2014;Zambrano-Bigiarini et al, 2017), despite their demonstrated superior performance in cold climates Beck et al, 2017b;. In addition, some studies re-used gauge observations already incorporated in some of the P datasets to determine their accuracy (e.g., Chen et al, 2013;Ashouri et al, 2016;Zambrano-Bigiarini et al, 2017), precluding independent validation.…”
mentioning
confidence: 99%
“…Studies have been extensively performed to evaluate different precipitation products (e.g., gauge-based, and reanalysis and remote sensing-related datasets) over the globe [98][99][100][101][102]. For example, Nair and Indu [99] noted that the MSWEP products (input for GLEAM3.0a) in India showed large errors in higher precipitation (i.e., >75th and >95th quantiles), which was confirmed by Alijanian et al [98] in Iran. Sun et al [102] found that the CPC-U precipitation (input for MERRA-Land) averaged over the world was underestimated for each season and correspondingly led to the annual value being the smallest compared to other datasets.…”
Section: Model Inputsmentioning
confidence: 80%
“…If a given ET model is ideally full-biophysical and, thus, can comprehensively describe the ET processes, errors in the ET estimates and differences among the ET products are mainly dependent on various inputs, especially for precipitation and radiation [36,54,60,75,76,79]. Studies have been extensively performed to evaluate different precipitation products (e.g., gauge-based, and reanalysis and remote sensing-related datasets) over the globe [98][99][100][101][102]. For example, Nair and Indu [99] noted that the MSWEP products (input for GLEAM3.0a) in India showed large errors in higher precipitation (i.e., >75th and >95th quantiles), which was confirmed by Alijanian et al [98] in Iran.…”
Section: Model Inputsmentioning
confidence: 99%